2018
DOI: 10.1371/journal.pone.0195011
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric interfaces as a tool in drug discovery: Specific interference with activity of malate dehydrogenase of Plasmodium falciparum in vitro

Abstract: Malaria remains a major threat to human health, as strains resistant to current therapeutics are discovered. Efforts in finding new drug targets are hampered by the lack of sufficiently specific tools to provide target validation prior to initiating expensive drug discovery projects. Thus, new approaches that can rapidly enable drug target validation are of significant interest.In this manuscript we present the crystal structure of malate dehydrogenase from Plasmodium falciparum (PfMDH) at 2.4 Å resolution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 45 publications
(78 reference statements)
1
26
0
Order By: Relevance
“…In order to validate the druggability of the targeted malate‐aspartate pathway, structure‐based mutagenesis experiments of the two involved genes were performed. We have recently demonstrated that a surface mutation in Pf MDH, where valine 190 was mutated into tryptophan, disrupted the A‐C interface as anticipated, causing significant activity loss (Lunev et al, ). Our previous data suggested that the introduction of the V190W mutation at the oligomeric interface (A‐C) not only caused the splitting of the tetramer into a pair of dimers but it also made the re‐formation of the tetramer highly unlikely due to the introduction of molecular clashes.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…In order to validate the druggability of the targeted malate‐aspartate pathway, structure‐based mutagenesis experiments of the two involved genes were performed. We have recently demonstrated that a surface mutation in Pf MDH, where valine 190 was mutated into tryptophan, disrupted the A‐C interface as anticipated, causing significant activity loss (Lunev et al, ). Our previous data suggested that the introduction of the V190W mutation at the oligomeric interface (A‐C) not only caused the splitting of the tetramer into a pair of dimers but it also made the re‐formation of the tetramer highly unlikely due to the introduction of molecular clashes.…”
Section: Discussionmentioning
confidence: 65%
“…Pf MDH possesses a tetrameric conformation where each monomer is comprised of 326 residues and is composed of two major domains: an N‐terminal cofactor‐binding domain containing a parallel structure of six beta‐sheets (Rossmann‐fold) and C‐terminal substrate‐binding domain. Our previous results suggested that a correctly formed tetrameric assembly of Pf MDH is essential for activity (Lunev et al, ). Indeed, the introduction of a tryptophan residue at one of the interfaces facilitating oligomerization (V190W) results in disruption of the tetramer, breaking it down into two dimers, and a significant reduction in activity.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations